Contributions to the larvae of North American Nixe (Ephemeroptera: Heptageniidae), with the description of N. dorothae sp. nov. from southern Indiana - Webb, J. M.; Mccafferty, W. P. (Zootaxa, 2011)
Nixe dorothae n. sp. (Ephemeroptera: Heptageniidae) is described from southern Indiana, USA based on larvae, males, and females. Larvae are easily differentiated from those of the other known North American species by the presence of two rows of denticles on the tarsal claws. Males are differentiated from congeners by the presence of median spines on the apical sclerites of the penes and reddish-brown abdominal terga. The larva of N. rusticalis is described for the first time; it is differentiated from known North American Nixe by having more than 15 comb setae on the maxilla. A preliminary key for the larvae of the known North American Nixe is provided.